The culture of design - Julier, Guy. (b)
What is the social impact of design? How do culture and economics shape the objects and spaces we take for granted? How do design objects, designers, producers and consumers interrelate to create experience? How do new networks of communication and technology change the design process?
Includes references and index.
Keywords: Design -- Social aspects; Industrial design -- Social aspects